The importance of transversal skills in higher education curricula for today's labor market - Almeida, F.; Simões, E.; Belchior-Rocha, H.; Casquilho-Martins, I. (12th International Technology, Education and Development Conference, 2018)
In the process of teaching and training, aligning learning goals with the needs of the labor market is a difficult task for universities. It is necessary to promote and develop generic skills that provide competitive advantages for students entering the job market. Although organizations seek professionals with flexible and varied skills, universities often underestimate the importance of cross-curricular skills. In addition, it is intended that the university promotes in the students' personal development through their academic, personal, social and professional adjustment. Organizations today tend to approach work globally and organically and it is increasingly important that any activity is framed in a global understanding of work processes and backed by up-to-date and specialized knowledge. These skills are a prerequisite for adapting to change and by promoting lifelong learning. In the transition from the university to the job market, in addition to technical and professional skills, it is essential to have personal and social skills such as communication, organization and time management, teamwork and conflict management, essential in this highly competitive context. Thus, this article aims to identify the perception of recent graduates as to the importance of the transversal competencies acquired and developed in the academic environment and what and how they are applied in the organizational environment. Answering the following question: How do students perceive competency training as a driver of competitive advantages for the challenges of the labor market world? Specifically, it aims to analyze the impact of the training in transversal competencies that occurred during the 1st cycle of higher studies on the promotion of competences in the work environment. The answers to a questionnaire to identify the perception of recent graduates on this issue allowed us to analyze the development and applicability of these competencies in the organizations. This analysis underlines the importance of transversal skills in the integration of young people into the labor market, and also highlights the importance of higher education's contribution to their acquisition and development. The results are further discussed in the broader framework of how universities adapt to the strong socio-economic changes that characterize current times.